Hypercalcemia from sarcoidosis successfully treated with infliximab - Huffdtutter, J.G.; Huffstutter, J.E. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Sarcoidosis is a systematic inflammatory condition with a variable clinical course.While many patients have a benign, indolent illness, some patients have more severe manifestations.Therapy is determined by an individual patient’s disease manifestations and the response to treatment.We report a case of sarcoidosis beginning with lymphadenopathy, initially controlled with steroids and immunosuppressive therapy. Our patient tolerated treatments poorly and developed severe hypercalcemia with progressive renal insufficiency. Intravenous infliximab was given with prompt resolution of hypercalcemia and very gradual improvement in renal function. Discontinuation of therapy resulted in immediate elevation of serum calcium. This patient has now responded for four years to infliximab treatment with no serious adverse events and continued improvement in renal function. Prompt infliximab therapy should be considered for patients with severe hypercalcemia from sarcoidosis unresponsive to steroids or other more conventional treatments.